Menjelajahi kearifan lokal: Arsitektur nusantara sebagai warisan budaya bangsa - Sulistyana, Anisya Noor (Maliki Interdisciplinary Journal, 2024)
Indonesia or Nusantara has a variety of interesting cultures to discuss, especially buildings left by our ancestors which can be used as lessons for the world of architecture. The aim of this research is to determine the variety of buildings inherited from our ancestors in terms of aesthetics and functions. The research method is library research method which is described descriptively. The results of this is research show that buildings in Nusantara were not just created just like that, but our ancestors also knew and understood how to build a building or a home that could provide comfortness, appropriate function, and also give a high quality of aesthetic value.